Age of the Barremian–Aptian boundary and onset of the Cretaceous Normal Superchron - Olierook, Hugo; Jourdan, Fred; Merle, Renaud (2019)
© 2019 Elsevier B.V. The age assigned to the boundary of the Barremian and Aptian stages remains one of the most poorly constrained post-Pangean stratigraphic boundaries. The lack of a Global Boundary Stratotype Section and Point (GSSP) for the stage boundary has hampered efforts to calibrate the absolute age of the Cretaceous period in the geological time scale. The current definition of the Barremian–Aptian boundary also approximates the onset of magnetic polarity chron M0r; the end of this chron denotes the start of the Cretaceous Normal polarity Superchron that is of fundamental importance for plate reconstructions. Currently, there is up to 5% discrepancy in the age estimates of the Barremian–Aptian boundary (ca. 126–121 Ma) and the start of the Cretaceous Normal Superchron. Here, we review available geochronological information from the late Barremian and early Aptian stages collected from the Pacific Ocean, China, California, the Ontong Java Nui large igneous province and the High Arctic large igneous province. By utilizing only robust geochronological data including U-Pb and recalibrated 40Ar/39Ar ages from sites with magnetic polarity information and/or paleontological constraints, we calculate a best estimate of between 123.8 and 121.8 Ma for the Barremian–Aptian boundary and the onset of chron M0r at 2σ confidence. Using estimates of the duration of chron M0r (0.49 ± 0.10 Myr, 2σ), we conservatively compute the start of the Cretaceous Normal Superchron to between 123.4 and 121.2 Ma (2σ). Using an age of 83.07 ± 0.15 Ma (2σ) for the end of the Cretaceous Normal Superchron, the duration of the superchron is also constrained to between 38.0 and 40.5 Myr (2σ). These age ranges for the Barremian–Aptian boundary, the onset of the Cretaceous Normal Superchron and the duration of the superchron currently provide the best estimates until a GSSP is formally ratified.